Sensitivity of tropical woodland savannas to El Niño droughts - S. Matias Reis; S. Matias Reis; Y. Malhi; B. H. Marimon Junior; B. Schwantes Marimon; H. Zhang-Zheng; I. Araújo; R. Freitag; E. Almeida de Oliveira; K. da Silva Peixoto; L. Januário de Souza; E. L. Souza da Silva; et al. (Biogeosciences)
The 2015–2016 El Niño event led to one of the hottest and most intense droughts for many tropical forests, profoundly impacting forest productivity. However, we know little about how this event affected the Cerrado, the largest savanna in South America. Here, we report on 5 years of productivity of the dominant vegetation types in the Cerrado, namely savanna (cerrado) and transitional forest–savanna (cerradão), continuously tracked before, during, and after the El Niño. Between 2014 and 2019, we carried out intensive monitoring of the productivity of key vegetation components (stems, leaves, roots). Cerradão productivity declined strongly by 29 % during the El Niño event. The most impacted component was stem productivity, which was reduced by 58 %. By contrast, cerrado productivity varied little over the years, and while the most affected component was fine roots, declining by 38 % during the event, fine-root productivity recovered soon after the El Niño. The two vegetation types also showed contrasting patterns in terms of the allocation of productivity to canopy, wood, and fine-root production. Our findings demonstrate that the cerradão can show low resistance and resilience to climatic disturbances due to the slow recovery of productivity. This suggests that the transitional Amazon–Cerrado ecosystems between South America's largest biomes may be particularly vulnerable to drought, enhanced by climate change.